Adherence to Mediterranean Diet and Non‐Alcoholic Fatty Liver Disease: Effect on Insulin Resistance. (December 2017) - Baratta, Francesco; Pastori, Daniele; Polimeni, Licia; Bucci, Tommaso; Ceci, Fabrizio; Calabrese, Cinzia; Ernesti, Ilaria; Pannitteri, Gaetano; Violi, Francesco; Angelico, Francesco; Del Ben, Maria
Abstract : Objectives: The prevalence of cardiometabolic disorders, including non‐alcoholic fatty liver disease (NAFLD), is increasing in western countries, because of changes in lifestyle and dietary habits. Mediterranean Diet (Med‐Diet) is effective for cardiovascular prevention, but its relationship with NAFLD has been scarcely investigated. Methods: We included 584 consecutive outpatients presenting with one or more cardiovascular risk factor such as type 2 diabetes mellitus (T2DM), arterial hypertension, overweight/obesity, and dyslipidemia. Liver steatosis was assessed using ultrasonography. Med‐Diet adherence was investigated by a validated semiquantitative nine‐item dietary questionnaire; patients were divided into low, intermediate, and high adherence. Insulin resistance was defined by the 75th percentile of homeostasis model of insulin resistance (HOMA‐IR; ≥3.8). Results: The mean age was 56.2±12.4 years and 38.2% were women. Liver steatosis was present in 82.7%, and its prevalence decreased from low to high adherence group (96.5% vs. 71.4%, P <0.001). In a multiple logistic regression analysis, hypertriglyceridemia (odds ratio (OR): 2.913; P =0.002), log (ALT) (OR: 6.186; P <0.001), Med‐Diet adherence (intermediate vs. low OR: 0.115; P =0.041, high vs. low OR: 0.093; P =0.030), T2DM (OR: 3.940; P =0.003), and high waist circumference (OR: 3.012; P <0.001) were associated with NAFLD. Among single foods, low meat intake (OR: 0.178; P <0.001) was inversely significantly associated with NAFLD. In 334 non‐diabetic NAFLD patients, age (OR: 1.035, P =0.025), high waist circumference (OR: 7.855, P <0.001), hypertriglyceridemia (OR: 2.152, P =0.011), and Log (ALT) (OR: 2.549, P =0.002) were directly associated with HOMA‐IR, whereas Med‐Diet score was inversely associated (OR: 0.801, P =0.018). Conclusions: We found an inverse relationship between Med‐Diet and NAFLD prevalence. Among NAFLD patients, good adherence to Med‐Diet was associated with lower insulin resistance. Our findings suggest that Med‐Diet may be a beneficial nutritional approach in NAFLD patients.